2009
DOI: 10.2215/cjn.02220409
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Vascular Disease–Related Procedures in Dialysis Patients

Abstract: Background and objectives: Peripheral vascular disease (PVD) is prevalent among dialysis patients, and many dialysis patients undergo PVD-related procedures. We aimed to examine the risk factors for and prognosis after such procedures in the dialysis setting.Design, setting, participants, & measurements: In a national prospective cohort study of 1041 incident dialysis patients, we examined the factors that are associated with PVD procedures (lower extremity amputations and bypasses) after the start of dialysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 31 publications
4
23
0
Order By: Relevance
“…44 As previously discussed that DM predisposes to micro-and macro-vascular complications, development of diabetic foot syndrome and also infections, 2,3 it would be ideal for these patients to have a tighter control of their blood sugar levels hence preventing worsening prognosis of foot complications which require LLAs. Our findings are consistent with other studies done previously; Plantinga et al 21 and Ishii et al 16 also found the association between high CRP levels while Plantinga et al's study along with Speckman et al 24 also reported the low levels of albumin amongst amputees, while LockingCustolito et al 17 found that elevated HbA1c was associated with LLAs. Our study was a retrospective chart audit and we were relying on the health professional's accuracy of information documented in patient medical records as well as biochemical pathology data base for our data collection.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…44 As previously discussed that DM predisposes to micro-and macro-vascular complications, development of diabetic foot syndrome and also infections, 2,3 it would be ideal for these patients to have a tighter control of their blood sugar levels hence preventing worsening prognosis of foot complications which require LLAs. Our findings are consistent with other studies done previously; Plantinga et al 21 and Ishii et al 16 also found the association between high CRP levels while Plantinga et al's study along with Speckman et al 24 also reported the low levels of albumin amongst amputees, while LockingCustolito et al 17 found that elevated HbA1c was associated with LLAs. Our study was a retrospective chart audit and we were relying on the health professional's accuracy of information documented in patient medical records as well as biochemical pathology data base for our data collection.…”
Section: Discussionsupporting
confidence: 93%
“…This could be true in the case of our study as all the subjects with LLA had concurrent DM which is strongly associated with foot ulceration. 12,25 On the other hand, the strong association between PAD and LLAs in the current study was reported by others 21 where calciphylaxis was thought to be a contributing factor. 15 Other risk factors for LLA identified in this study include peripheral neuropathy and retinopathy as previously reported.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…7,8 Limited available data also suggest that PAD is prevalent in hemodialysis patients 4,[9][10][11][12] and is associated with poor outcomes. 4,6,13 However, the studies on the role of PAD in predicting mortality in peritoneal dialysis patients are even less. [14][15][16] Liu et al 17 recently reported that the prevalence of PAD is high and is associated with total mortality in 153 Taiwan Peritoneal Dialysis (PD) patients; however, the patients with PAD were much older than non-PAD peers (64.3 years vs. 52.1 years, p < 0.001).…”
Section: Introductionmentioning
confidence: 99%